1952. Evaluation of Relapse and Reinfection Using Whole-Genome Sequencing of Clostridium difficile Isolates From Elderly Patients With C. difficile Infection (CDI) in the EXTEND Randomized, Controlled, Comparative Study of Extended-Pulsed Fidaxomicin and Vancomycin for the Treatment of CDI. (26th November 2018) - Wilcox, Mark; Cornely, Oliver A; Guery, Benoit; Longshaw, Chris; Georgopali, Areti; Karas, Andreas; Kazeem, Gbenga; Palacios-Fabrega, Jose Alejandro; Vehreschild, Maria J G T
Abstract: Background: The EXTEND study demonstrated reduced 90-day recurrence rates for an extended-pulsed regimen of fidaxomicin (EPFX) vs. standard vancomycin (SV) in the treatment of Clostridium difficile infection (CDI): treatment difference −13%, P = 0.00073. 1 Whole-genome sequencing (WGS) is used to differentiate between same-strain relapse and new-strain reinfection of CDI. We used WGS of paired C. difficile samples from patients with CDI recurrence in the EXTEND study to assess EPFX and SV in relation to relapse and reinfection. Methods: Patients aged ≥60 years with CDI were randomized (1:1) to receive either EPFX (fidaxomicin 200 mg tablets, twice daily on Days 1–5 and once daily on alternate days on Days 7–25) or SV (125 mg capsules, four times daily on Days 1–10). Paired stool samples were collected from all patients at screening and from patients with recurrence after test-of-cure (TOC). Recurrence was defined as diarrhoea occurring to a greater extent than the frequency recorded at TOC, and confirmed positive for C. difficile toxin A/B and requiring further CDI therapy. C. difficile isolates from paired samples underwent WGS and single nucleotide variant (SNV) difference analysis. Paired samples with ≤2 SNV differences were considered relapses, paired samples with >10 SNV differences were considered reinfection, and those with >2 but ≤10 SNV differences (or without WGS) were considered indeterminate. Results: At Day 90, 11/177 (6%) patients in the EPFX arm and 34/179 (19%) patients in the SV arm had CDI recurrence. Of these, samples from 7/11 EPFX- and 19/34 SV-treated patients were available for paired WGS analysis. SNV analysis showed that most CDI recurrences were new-strain reinfections (table). Conclusion: Most recurrences were reinfections, but small sample sizes limited definitive conclusions. Reference 1. Guery et al. (2017). Lancet Inf Dis 18:296–307. Disclosures: M. Wilcox, Astellas Pharma: Consultant and Grant Investigator, Consulting fee, Research grant, Speaker honorarium and This study was initiated and sponsored by Astellas. Medical writing support was provided by Cello Health MedErgy and funded by Astellas. O. A. Cornely, Astellas Pharma: Grant Investigator, Lecture speaker and Scientific Advisor, Research grant, Speaker honorarium and This study was initiated and sponsored by Astellas. Medical writing support was provided by Cello Health MedErgy and funded by Astellas. B. Guery, Astellas Pharma: Consultant, Consulting fee and This study was initiated and sponsored by Astellas. Medical writing support was provided by Cello Health MedErgy and funded by Astellas. C. Longshaw, Astellas Pharma: CL was a full-time employee of Astellas Pharma, Inc., during the study conduct and is now an employee of Shionogi Europe Ltd.; he also has a patent WO2015169451 A1 pending. and Employee, Medical writing support was provided by Cello Health MedErgy and funded by Astellas and Salary. A. Georgopali, Astellas Pharma: Employee, Medical writing support was provided by Cello Health MedErgy and funded by Astellas. and Salary. A. Karas, Astellas Pharma: AK has patents WO2015169451 A1 and EP17167541.6 pending. and Employee, Medical writing support was provided by Cello Health MedErgy and funded by Astellas. and Salary. G. Kazeem, Astellas Pharma: Independent Contractor, Medical writing support was provided by Cello Health MedErgy and funded by Astellas. and Salary. J. A. Palacios-Fabrega, Astellas Pharma: AP-F has a patent EP17167541.6 pending. and Employee, Medical writing support was provided by Cello Health MedErgy and funded by Astellas. and Salary. M. J. G. T. Vehreschild, Astellas Pharma: Consultant and Grant Investigator, Consulting fee, Grant recipient and This study was initiated and sponsored by Astellas. Medical writing support was provided by Cello Health MedErgy and funded by Astellas.